(untitled) (Economic and Political Thought, 2019)
The objective of this paper is to propose such directions of Poland’s foreign policy and security policy in the Euro-Atlantic zone after 2018 which would maximise opportunities and minimise threats identified in the assessment of the country’s internal considerations on the one hand, and status of Poland’s bilateral relations with individual countries, Poland’s multilateral relations with NATO and the European Union and developments in the international politics worldwide in 1999–2018 on the other. Given the predefined limitations as to the length of this study, the objective has been achieved through: (i) a discussion of Poland’s selected objective internal considerations (geography; demographic, economic and military potentials); (ii) an analysis of Poland’s relations with Germany, France, the US, Belarus, Ukraine and Russia, as well as Poland’s contractual interrelations with NATO and the European Union; (iii) attempt at classifying these considerations and factors into opportunities and threats; (iv) description of such proposed directions of Poland’s foreign policy and security policy in the Euro-Atlantic zone after 2018 which would maximise opportunities/minimise threats thus identified. The analysis assumes the following research hypothesis: changes in the international environment, as well as in Poland’s bilateral and multilateral international relations render it necessary to revise and adjust directions of Poland’s foreign policy and security policy so that Poland’s position both within Europe and globally would be rebuilt, and that Poland’s security would be enhanced.